Settling behaviors of microplastic disks in water - Yang, Ge; Yu, Zijian; Baki, Abul B. M.; Yao, Weiwei; Ross, Matthew S.; Chi, Wanqing; Zhang, Wenming (My University, 2023)
Microplastic (MP) disks have not been studied for settling behaviors in aquatic environments, which affects the transport and fate of MPs. Therefore, settling experiments were conducted on MP disks of three shapes and four common-seen materials. Lighter MP disks (with density ρs = 1.038 g/cm3 and length l ≤ 5 mm) followed rectilinear vertical trajectories, while heavier MP disks (ρs = 1.161–1.343 g/cm3 and l = 5 mm) followed zigzag trajectories with oscillations and rotations. The mean terminal settling velocities of MP disks were 19.6–48.8 mm/s. Instantaneous settling velocities of heavier MP disks fluctuated. Existing formulas could not accurately predict the settling velocity of MP disks; thus, a new model was proposed with an error of 15.5 %. Finally, the Red - I* diagram (Red is the disk Reynolds number and I* is the dimensionless moment of inertia) was extended for MP disks to predict settling trajectories.
Keywords: microplastic disks; settling velocity; trajectory; secondary motion